Privacy-Enhanced Deduplication Technique in Closed Circuit Television Video Cloud Service Environment - Park, Namje; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: With the recent surging popularity of cloud services, various cloud service providers (CSP) are coming into the picture. On cloud platforms, many different forms of services are available, among which storage-based solutions are the most commonly adopted. The cloud storage market also is likely to continue to expand in the future.Methods/Statistical analysis:Presently, quite a few cloud storage environments are already implementing the deduplication technique. Given the characteristics of cloud environments, storage servers capable of accommodating large quantities of storage are necessary. With increases in storage capacity emerges the need for additional storage solutions. Utilizing deduplication can solve the cost problem fundamentally.Findings:The privacy problem can be extremely serious if the files in question deal with â€œsensitiveâ€ issues such as political orientation, ideas, particular diseases, and sexuality. When the list of the file uploaders is obtained on the cloud server, the cloud environment itself may act as a surveillance system in the future, hence the unavoidable risk.Improvements/Applications:This paper indicates the privacy breach problem and proposes a new technique of deduplication to solve it. In the proposed technique, the map structures of the user and files are not stored on the server and thus the list of file uploaders cannot be secured through the analysis of meta-information on the server, hence the privacy of the users intact. Furthermore, the new technique can solve the issue of file ownership by using PIN (Personal Identification Number) and offers merits such as safety against insider breaches and sniffing attacks.Â Â Â